2018
DOI: 10.1177/1060028017751913
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Persistence Among Insured Patients Newly Starting Buprenorphine/Naloxone for Opioid Use Disorder

Abstract: Several health care delivery and use variables were significantly associated with nonpersistence. Concomitant use of prescription opioids is the most easily modifiable risk factor that health care providers and policy makers may act on to improve treatment continuation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 34 publications
1
27
0
Order By: Relevance
“…First, we would like to point out that opioid medications are associated with increased discontinuation risk of buprenorphine, although not statistically significant using naltrexone as a comparison drug (table 3). In our analysis, many of the patients on MOUD are prescribed with codeine, fentanyl, hydrocodone, morphine, oxycodone and tramadol; and similar statistics are observed by Shcherbakova et al (2018). Overprescribing of opioid medications is believed to be a major cause for the current opioid epidemic (Manchikanti et al, 2012).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…First, we would like to point out that opioid medications are associated with increased discontinuation risk of buprenorphine, although not statistically significant using naltrexone as a comparison drug (table 3). In our analysis, many of the patients on MOUD are prescribed with codeine, fentanyl, hydrocodone, morphine, oxycodone and tramadol; and similar statistics are observed by Shcherbakova et al (2018). Overprescribing of opioid medications is believed to be a major cause for the current opioid epidemic (Manchikanti et al, 2012).…”
Section: Discussionsupporting
confidence: 71%
“…Subsequently, risk factors for discontinuation of buprenorphine are investigated. These studies include Lopian, Chebolu, Kulak, Kahn, & Blondell (2019), Manhapra, Agbese, Leslie, & Rosenheck (2018), Morgan et al (2018), Saloner et al (2017), Samples et al (2018), and Shcherbakova et al (2018) etc. Risk factors in these studies include demographic variables, administrative factors (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Opiate substitution treatment was consistently associated with a lower frequency of ED presentation and hospital admission than comparison groups of untreated opiate users. Among substitution patients, consistent medication was associated with a lower rate of ED utilization . Some studies looked at different types of treatment.…”
Section: Resultsmentioning
confidence: 99%
“…While the treatment of OUD with OST improves outcomes compared to no treatment, there is a wide range of the overall success of OST, depending on what time period is being reported. Two recent reports indicated that~40% of patients treated with buprenorphine were retained in OST treatment for 1 year [12,13]. There are some known demographic, socioeconomic, and psychosocial contributors to the retention of individuals in MAT, based mostly on research in methadone-based OST.…”
Section: Improving Successful Opioid Substitution Therapymentioning
confidence: 99%